2014
DOI: 10.1111/jop.12203
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin, E‐cadherin, β‐catenin, and CD44v6 in recurrent ameloblastoma: their distribution patterns and relevance

Abstract: Podoplanin, β-catenin, and CD44v6 upregulation at the tumor invasive fronts in RA and UPA supports a differential regulatory role by these molecules in mediating collective cell migration and local invasiveness. E-cadherin downregulation suggests altered cell adhesion function during tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Moreover, as a sign of active EMT, we found an increased cytoplasmic reactivity for vimentin and a prevailing nuclear Twist 1 and Slug 1 expression in tumor cells, especially at the tumor’s advancing edge. Our results were confirmed in the literature by cases of ameloblastomas, where it was also been noticed an E-cadherin downregulation simultaneously with an upregulation of podoplanin, β-catenin, and CD44v6 at the tumor advancing edges, suggesting their involvement in mediating collective cell migration and local invasiveness [29]. Moreover, it has been reported that transcription factors such as Snail, Slug, SIP1, and Twist could have differential roles in mediating local invasiveness in ameloblastomas [30].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, as a sign of active EMT, we found an increased cytoplasmic reactivity for vimentin and a prevailing nuclear Twist 1 and Slug 1 expression in tumor cells, especially at the tumor’s advancing edge. Our results were confirmed in the literature by cases of ameloblastomas, where it was also been noticed an E-cadherin downregulation simultaneously with an upregulation of podoplanin, β-catenin, and CD44v6 at the tumor advancing edges, suggesting their involvement in mediating collective cell migration and local invasiveness [29]. Moreover, it has been reported that transcription factors such as Snail, Slug, SIP1, and Twist could have differential roles in mediating local invasiveness in ameloblastomas [30].…”
Section: Discussionsupporting
confidence: 87%
“…Also, in the present study we have observed a podoplanin expression at the advancing edge, mainly at the periphery of tumor proliferations, suggesting its involvement in tumor invasiveness. In fact, it is well known that this transmembrane sialomucin is involved in odontogenesis and in promoting local invasion of various odontogenic tumors [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, a few connective tissue cells were weakly positive for podoplanin in a limited number of cases. The lack of podoplanin immunostaining in ectomesenchymal elements of AF and OM and fibrous wall of COC and the “variable” podoplanin expression in ameloblastoma‐fibroblasts has also been reported previously. Further research is required to clarify this issue.…”
Section: Discussionsupporting
confidence: 74%
“…Canonical Wnt ligands (Wnt-1, 2, 3, 8a, 8b, 10a, and 10b) were reported to be expressed in 100% of ameloblastomas (n=72) representing unicystic, solid/multicystic, and desmoplastic subtypes, and including 10 cases of recurrent ameloblastoma (Siar 2012). The expression of β-catenin, the signal transducer of canonical Wnt signaling, is inconsistently reported, with expression detected by immunohistochemistry in 15–100% of ameloblastomas [6269]. Overall, 82% of ameloblastomas express β-catenin (n=137).…”
Section: Wntmentioning
confidence: 99%